Regulated Cell Death of Alveolar Macrophages in Acute Lung Inflammation: Current Knowledge and Perspectives - Xia S; Gu X; Wang G; Zhong Y; Ma F; Liu Q; Xie J (Journal of Inflammation Research)
Siwei Xia, Xiaoyan Gu, Gaojian Wang, Yizhi Zhong, Fengjie Ma, Qinxue Liu, Junran Xie Department of Anesthesiology, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaCorrespondence: Junran Xie, Department of Anesthesiology, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China, Email xiejunran@zju.edu.cnAbstract: Acute lung injury/acute respiratory distress syndrome (ALI/ARDS) is a common and serious clinical lung disease characterized by extensive alveolar damage and inflammation leading to impaired gas exchange. Alveolar macrophages (AMs) maintain homeostatic properties and immune defenses in lung tissues. Several studies have reported that AMs are involved in and regulate ALI/ARDS onset and progression via different regulated cell death (RCD) programs, such as pyroptosis, apoptosis, autophagic cell death, and necroptosis. Notably, the effects of RCD in AMs in disease are complex and variable depending on the environment and stimuli. In this review, we provide a comprehensive perspective on how regulated AMs death impacts on ALI/ARDS and assess its potential in new therapeutic development. Additionally, we describe the crosstalk between different RCD types in ALI, and provide new perspectives for the treatment of ALI/ARDS and other severe lung diseases.Keywords: alveolar macrophage, apoptosis, autophagic cell death, necroptosis, pyroptosis, acute lung injury